Forearm EMG during rock climbing differs from EMG during handgrip dynamometry - Watts, P. B.; Jensen, R. L.; Gannon, E.; Kobeinia, R.; Maynard, J.; Sansom, J. (International Journal of Exercise Science, 2008)
Handgrip dynamometry is often given importance in the study of rock climbing performance. Whether handgrip dynamometry produces a degree of muscle activation comparable to actual climbing has not been reported. Furthermore, the degree and variability of muscle activation for various hand configurations during climbing are unknown. The purpose of this study was to record forearm EMG responses for six hand configurations during climbing and to compare these responses to a maximum handgrip test. Five experienced climbers performed four moves up (UP) and down (DN) on an overhanging 45-deg. climbing wall with each of six hand configurations: crimp (C), pinch (P), three 2-finger combinations (2F1, 2F2, 2F3) and an open-hand grip (O). Forearm EMG was recorded via surface electrodes. Data were recorded for the second UP and second DN moves. Prior to climbing, maximum handgrip force (HG) and simultaneous EMG were obtained. Mean HG force was 526.6±33.3 N. Times to complete the climbing movements with each hand configuration varied between 3.1±0.5 and 4.8±0.9 sec with no significant differences. Peak EMG`s during climbing were higher than HG EMG (p<.05). Mean EMG amplitudes for UP, as percentages of HG EMG, were 198±55, 169±22, 222±72, 181±39, 126±32, and 143±47% for C, P, 2F1, 2F2, 2F3, and O respectively. Significant differences were found for O versus 2F1 and for 2F3 versus 2F1 and C (p<.05). EMG amplitudes were lower for DN than UP (p<.05). Since all climbing EMGs exceeded HG EMG, it was concluded that handgrip dynamometry lacks specificity to actual rock climbing.